2013
DOI: 10.1002/jnr.23320
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage and amyloid‐β metabolism in brain regions of the longest‐lived rodents

Abstract: Naked mole rats (NMRs) are the longest-lived rodents, with young individuals having high levels of Aβ in their brains. The purpose of this study was twofold: to assess the distribution of Aβ in key regions of NMR brains (cortex, hippocampus, cerebellum) and to understand whether the accumulation of Aβ is due to enhanced production or decreased degradation. Recent evidence indicates that lipid peroxides directly participate in induction of cytoprotective proteins, such as heat shock proteins (Hsps), which play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 59 publications
(55 reference statements)
2
38
0
Order By: Relevance
“…While there are multiple β-subunits in eukaryotes, unlike in prokaryotes that have only one type, the reduced phosphorylated states in the oldest NMR brains could suggest that there is an increased affinity towards proteome assembly and therefore, an increased degradation of unwanted or damaged proteins, clearing the cell of detritus to promote healthy cellular function. This observation would be consistent with the observed high levels of proteasome activity reported for brain lysates of the NMR [8]. …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While there are multiple β-subunits in eukaryotes, unlike in prokaryotes that have only one type, the reduced phosphorylated states in the oldest NMR brains could suggest that there is an increased affinity towards proteome assembly and therefore, an increased degradation of unwanted or damaged proteins, clearing the cell of detritus to promote healthy cellular function. This observation would be consistent with the observed high levels of proteasome activity reported for brain lysates of the NMR [8]. …”
Section: Discussionsupporting
confidence: 92%
“…Previously, we have shown that a particular UCH variant, UCHL1, is oxidized in AD brain, which could conceivably inhibit Aβ degradation [66, 67]. However, it has been reported that even though NMRs exhibit Aβ levels similar to that of 3xTg-AD mice, there is no accumulation of senile plaques in the NMR brain [8, 68]. Moreover, in mice ubiquitinylated proteins accumulate with age; however, in NMRs levels of ubiquitinylated proteins of 2 year-old and 26 year-old rodents were similar [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to these declines in proteolytic degradation processes, the proteasome-mediated protein degradation system (PMDS), that includes both ubiquitin-dependent and independent proteasome machinery and associated molecular chaperones, is more robust in naturally long-lived species (Rodriguez et al, 2012; Edrey et al, 2014), long-lived mutants (Kruegel et al, 2011), calorically-restricted animals (Bonelli et al, 2008), and centenarians (Chondrogianni et al, 2000). As such it appears hard to reconcile a decline in proteasome function with rapamycin-induced extended longevity.…”
Section: Introductionmentioning
confidence: 99%
“…AD is the most common neurodegenerative disease causing dementia and having no treatment or cure as yet [158]. Although the exact physiopathology of AD is still unsettled, it is clear that brain dysfunctions and atrophy (due to neuronal loss) that accompany AD are correlated with the accumulation of unfolded proteins that tend to form neurotoxic protein aggregates, such as extracellular deposition of amyloid plaques, accumulation of intracellular neurofibrillary tangles (NFTs), inflammation, and oxidative stress [159][160][161]. Abundant extraneuronal deposits of amyloid-beta (Aβ) are the major pathological hallmark of AD and play an early pathologic role in the development of the disease [162].…”
Section: Suppression Of the Heat Shock Response In Agerelated Degenermentioning
confidence: 99%